Preparation and application of effective different catalysts for simultaneous control of diesel soot and NOX emissions: An overview - Dhal G.C.; Mohan D.; Prasad R. (My University, 2025)
Soot particulates and nitrogen oxides (NOX) from diesel engine exhaust have been causing serious problems to human health and the global environment. NO contributes not only to the production of acid rain but also to the production of photochemical smog in a reaction with hydrocarbons while under the influence of sunlight. Fine soot particulates (C8H to C10H), which contain mutagenic hydrocarbons, can easily reach far down into lung tissues when inhaled and therefore have a detrimental impact on human health. Diesel engines are the primary power source of vehicles used in heavy duty applications. These include two wheelers, buses, large trucks, and inside-highway construction and mining equipment. Furthermore, diesel engines are becoming an increasing part of the light duty vehicle market worldwide. In India, 100% of heavy duty vehicles, 60% of light-duty commercial vehicles and 20% of passenger cars are diesel powered. Diesel exhaust is inherently low in the concentration of CO and unburned HC, for NO and particulate matter are being objectionable to be removed from the exhaust. Since the reduction of both NO and soot particulate emissions to the allowed level cannot be accomplished by engine modifications alone, after-treatment activity for the simultaneous reduction of emissions should be developed. © 2017 The Royal Society of Chemistry.